Mushaf Al-Qur’an Nusantara: Perpaduan Islam dan Budaya Lokal - Lestari, Lenni (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2016)
Crystalization of statement ?Al-Qur?an will be protected all the time? has been totally convinced and created by any form. One of them is the tradition of Al-Qur?an writing and printing. Circumstancially, this phenomenon indicated the development of living Qur?an. This paper will discuss about the development of Mushaf Al-Qur?an of Indonesia, from the tradition of hand writing until digital era. Beside it, this paper will also analyze the phenomenon of Mushaf of Al-Qur?an in Indonesia, in the concept of living Qur?an, by reception of hermeneutic, aesthetic and cultural. This paper concludes; the development of writing and printing Al-Qur?an, includes hand writing and digitalization era, is the tradition has been always preserved by Indonesian people. As a kind of living Qur?an, the Mushaf of Indonesia is a evidence of the achievement of cultural transformation and a good civilization.